Reduced complexity optimum detector for block data transmission systems - S. P. K., Babu; M. F. M., Salleh; Farid, Ghani (The Institute of Electronics, Information and Communication Engineers, 2010)
Link to publisher's homepage at http://www.elex.ieice.org/